Devanka Diaz’s Creative Process of the Pas Ma Responsabilité Dance Work - Devanka Diaz Ayu Pitaloka; Soemaryatmi Soemaryatmi (Universitas Negeri Semarang, 2023)
This research reveals the creative process of creating Pas Ma Responsabilité dance work, starting from the discovery of ideas and concepts to the forms of presentation with a creative background in contemporary works. The research method used is qualitative with descriptive analysis using the practice-led approach where the practice of writing goes concurrently with data collection techniques through field studies and literature studies. This research produces a description of the creative process of creating the Pas Ma Responsabilité dance work which is revealed based on the existing theory and the processes that occur directly in the field. The creative process consists of preparation, in the form of data collection and an exploratory process with creative and divergent thinking; incubation, the process of settling and understanding data until appearing inspiration; illumination, the exploration stage of movement, expression, potential, technique, and character; verification, the stage when the idea or new creation must be tested against reality. This research can be used as a critical reference for discussing novelty in today's contemporary dance. The main framework in this paper used as a reference is the creative processes and the results of the field practice process.